REPETISI DALAM PUISI AL-QASIDATU AL-MUTAWAHHISHAH DAN QITTATI ASH-SHAMIYYAH KARYA NIZAR QABBANI: KAJIAN STILISTIKA التكرار في شعر القصيدة المتوحشة والقطاطي الشامية لنزار قباني: دراسة أسلوبية - Allisya Rizky Islami; Komarudin, Edi; Mawardi, Mawardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the use of repetition as a stylistic device in Al-Qaṣīdatu al-Mutawaḥḥishah and Qiṭṭatī ash-Shāmiyyah by Nizar Qabbani through a stylistic approach. The objectives of this study are to identify the types of repetition employed in the poems and to explain their stylistic functions. This research uses a qualitative descriptive method with observation and note-taking techniques. The data consist of words, phrases, and sentences containing repetition in both poems. The analysis is based on Gorys Keraf's theory of repetition, which includes anaphora, epistrophe, mesodiplosis, symploce, epizeuxis, tautotes, epanalepsis, and anadiplosis. The findings reveal five types of repetition: 13 instances of anaphora, 3 instances of epizeuxis, 7 instances of mesodiplosis, 4 instances of epistrophe, and 2 instances of symploce. The repetition found in both poems functions to emphasize meaning, strengthen emotional expression, build the lyrical persona’s inner atmosphere, create poetic rhythm, and enhance aesthetic value. In Al-Qaṣīdatu al-Mutawaḥḥishah, repetition is predominantly used to express anxiety, longing, and the desire for freedom. In contrast, in Qiṭṭatī ash-Shāmiyyah, repetition reinforces intimacy, protection, and emotional closeness. Therefore, repetition serves not only as a linguistic pattern of recurrence but also as an important stylistic element in constructing meaning and poetic beauty.